Long-Term Effects of Antiseizure Medications - LoPinto-Khoury, Carla (Seminars in Neurology, 2022)
Most patients with epilepsy will benefit from seizure control with one of an array of chronic antiseizure medications. Knowledge of the potential long-term effects of these medications is critical to prevent adverse consequences on overall health. Antiseizure medications vary in their capacities to affect the brain and peripheral nerves, hormones, bone mineralization, cardiovascular risk, renal health, hepatic, hematological, and dermatological systems. Understanding of pathophysiology and population risk has evolved, although most of the data available are still on older generation antiseizure medications such as phenytoin, carbamazepine, and valproic acid. The enzyme-inducing properties of some antiseizure medications make their effects on cardiovascular risk and bone health detrimental. Few clear guidelines exist for monitoring long-term effects of medication therapy for epilepsy. When selecting an antiseizure medication, consideration should be given to the individual patient's risks of adverse consequences on other organ systems. During monitoring of patients on chronic therapy, screening tools such as metabolic panels and bone density measurements can help stratify risk and guide management.
Keywords: antiseizure medication; epilepsy treatment; antiepileptic; anticonvulsant; seizure treatment